Proteomics identification of overexpressed serum proteins in dogs with Babesia canis infection - Sudpatchara Ritchoo; Phattara‐orn Havanapan; Metita Sussadee; Cherdsak Maneeruttanarungroj; Rucksak Rucksaken (Veterinary World, 2023)
Background and Aim: infection in dogs by examining the expressed serum protein profiles using proteomics. Materials and Methods: -infected dogs diagnosed using blood smear and polymerase chain reaction. We analyzed the proteins using two-dimensional gel electrophoresis. The candidate spots from the gel were subjected to protein identification using a nano-liquid chromatography system coupled to an ion-trap mass spectrometer equipped with an electrospray ionization nano-sprayer. Results: We found that 10 protein spots were overexpressed in the serum samples from infected dogs compared with healthy dogs, which corresponded to three proteins: serotransferrin, serotransferrin isoforms X1, and hemopexin. Furthermore, analysis of the protein-protein interaction network confirmed that they strongly interacted with each other. Conclusion: infection, making these proteins potential candidates for the development of diagnostic molecules or vaccines.
Keywords: Vector-borne infectious diseases; Advanced Proteomics Techniques and Applications; Advanced Biosensing Techniques and Applications